Női munka a falusi szabadság határai közt: huszadik századi pályaképek Besenyőtelekről - Őrszigethy, Erzsébet (Tér és Társadalom, 1993)
In villages, which have survived the proletarization processes in the twentieth century, women's job decisions are conditioned by the history of the local community. In the 1990s it is neither the currently poor labour demand, nor the individual ambitions, which determine whether a rural woman becomes a black employee or an entrepreneur in the labour market. Traditions, local social arrangements and economic circumstances together form major women's roles. I investigatecl women's careers in Besenyőtelek, Heves County, which has 3,000 inhabitants and perhaps has never been an "authentic" peasant village in its modern history. Between the two world wars, affluent peasants, artisans, merchants and servants lived here, but several declassed noblemen, bunglers, casual dealers, and out-migrating navvies also inhabited this village. The top of the social hierarchy was occupied by 50-60 land-owners whereas at the bottom one could find the army of agricultural servants and laborer. What sorts of job were women given in this structure of local society? In fact, the range of female occupations might have been more nuanced than the general local social milieu would suggest. In the first half of the century, women's desires did not favor emancipation as those were considered lucky who became their husbands' or families' "joined parts" or "dependents". Yet, this career was open for only few; due to economic reasons, the majority of women were forced to work outside the family production. This unwanted sovereignty has taught women a variety of occasional and "ad hoc" jobs and trained them to behave as independent workers. In the second half of the century, the job market became more standardized and constrained. In the lant four or five decades, women shifted from causal jobs to permanent employment while the family remained a safe "ferry" for them. Through a series of career-histories and lifeway-interviews one can learn that the "housewife" (different maternity allowances) status has appeared as the most common occupation for women up to the present. Whether this status turns to be a temporary or permanent condition depends on women's education, knowledge, age as well as the economic circumstances and ambitions of their families (e.g. the husband's occupation). In this study I intend to portray the basic conditions that women encounter in the local labour market at Besenyőtelek.